2012
DOI: 10.1088/0957-4484/23/47/475707
|View full text |Cite
|
Sign up to set email alerts
|

Green light emission from terbium doped silicon rich silicon oxide films obtained by plasma enhanced chemical vapor deposition

Abstract: The effect of silicon concentration and annealing temperature on terbium luminescence was investigated for thin silicon rich silicon oxide films. The structures were deposited by means of plasma enhanced chemical vapor deposition. The structural properties of these films were investigated by Rutherford backscattering spectrometry, transmission electron microscopy and Raman scattering. The optical properties were investigated by means of photoluminescence and photoluminescence decay spectroscopy. It was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
(28 reference statements)
4
24
1
Order By: Relevance
“…Figure 2(a) shows a strong emission from the SRSO matrix at 550 nm. We attributed this emission to the radiative recombination of defect states in the SRSO matrix or from very small amorphous nanoclusters 21 because Raman spectroscopy studies 18 have indicated that Si-NCs were not present at this Si concentration. Typically, one may expect to find a few potential defect states (e.g., NBOHC, oxygen deficient center (ODC), or the self-trapped exciton (STE)) in silica based materials such as SRSO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2(a) shows a strong emission from the SRSO matrix at 550 nm. We attributed this emission to the radiative recombination of defect states in the SRSO matrix or from very small amorphous nanoclusters 21 because Raman spectroscopy studies 18 have indicated that Si-NCs were not present at this Si concentration. Typically, one may expect to find a few potential defect states (e.g., NBOHC, oxygen deficient center (ODC), or the self-trapped exciton (STE)) in silica based materials such as SRSO.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent paper, 18 we have shown that emission from Tb 3þ ions in an SRSO matrix can be observed at UV excitation and its intensity strongly depends on the Si concentration and annealing temperature. Surprisingly, it has been shown that only samples close to stoichiometric SiO 2 (35 at.…”
Section: That the Energy Band Gap (Homo-lumo) Ofmentioning
confidence: 93%
“…Therefore, we expect deep defect levels in our material, an assumption that is supported by the observed broad emission in the spectra. This emission is coming from the absorption (and thus excitation) and subsequent relaxation of defect states, and provides no emission when the amount of non-radiative paths is too large (as happens in the asdeposited sample); on the contrary, the emission enhancement at higher temperatures is due to a reduction of non-radiative defects while activating radiative ones (which, as observed by PL, requires high annealing temperatures), reaching a maximum emission at 700 C; higher annealing temperatures improve the long-range atomic ordering of the oxide matrix (i.e., its structural arrangement), 14 consequently reducing the overall presence of defects and thus decreasing their emission. The situation is slightly different for Tb 3þ ions emission: in this case, in order to excite optically active Tb 3þ ions, the excitation energy must match the transition energy involving the 5 D 4 electronic level (i.e., resonant conditions).…”
Section: B Optical Emission Of Al-tb/sio 2 Filmsmentioning
confidence: 98%
“…5,9 In addition, REs have been employed to develop light-emitting silicon-based materials for optoelectronic applications. 10,11 With this aim, several works have reported on RE-doped oxides such as SiO 2 , Sirich silicon oxide, [12][13][14] or Si-rich silicon oxynitride 15 matrices as potential candidates to become active layers in lightemitting devices. The interest in determining the optical and electronic properties of the different RE species lies in the particular electronic structure they present, which allows engineering the desired emission spectra of the active layer.…”
Section: Introductionmentioning
confidence: 99%
“…The EL rise time values at different charge fluxes range from 0.5 ms to 0.7 ms, whereas the EL decay time was found to be 0.5 ms, which is close to the one measured under optical pumping in Tb 3þ :SiO 2 films. 20 The inset of Fig. 3 depicts the linear relationship between the inverse rise time and charge flux.…”
mentioning
confidence: 99%